Should Home‐Based Contraceptive Dispensing become a Routine part of Public Health Nurse Practice? Review of Nurse Perceptions. Issue 6 (7th September 2014) - Jacob‐Files, Elizabeth; Rdesinski, Rebecca; Storey, Marni; Gipson, Teresa; Cohen, Deborah J.; Olds, David; Melnick, Alan
Abstract Objective We examined public health nurses' beliefs about the safety of dispensing hormonal contraceptives in the home, the extent to which they considered contraceptive dispensing within their scope of practice, and the types of support needed to effectively dispense contraceptives in the home. Design and Sample We conducted focus groups in Washington State with 24 home visiting nurses participating in a Nurse Family Partnership (NFP) randomized clinical trial in which nurses dispensed hormonal contraceptives during home visits. Measures We assessed the feasibility of the intervention and barriers and facilitators to home dispensing of hormonal contraceptives. Results Nurses were, on average 52 years old and had been working in nursing approximately 25 years, with between 5 and 18 years of experience working in a family planning setting. Overall, nurses believed that, with the right training and support, dispensing of hormonal contraceptives in the home was safe and fit within their scope of practice. Those nurses who reported resistance to the intervention cited inadequate training, lack of clear protocols, and sufficient support as important deterrents. Conclusions Home‐based contraceptive dispensing by nurses is a feasible enhancement of the NFP program. To ensure that nurses are confident and able to dispense hormonal contraceptives, training, clinical protocols, consultation, and logistical support are needed.